Antifungal activity of allamanda cathartica stem and leaf crude extracts against pyricularia oryzae pathogen of rice blast disease / Khairun Nur Ali - Ali, Khairun Nur (2018)
This study presents the potential use of natural product from Allamanda cathartica leaves and stems extract, as biofungicides and their antifungal activity against Pyricularia oryzae pathogen of rice blast disease in vitro and in vivo. The objectives of the study are to observe and evaluate the mechanisms of antifungal activity of A. cathartica leave and stem crude extracts against P. oryzae, pathogen of rice blast disease microscopically and to determine the phytochemical constituent in the A. cathartica leave and stem crude extracts that act as an antifungal activity agent. The results from the experiments revealed that chloroform and methanol stem extracts of A. cathartica possessed fungistatic or fungicidal properties on the growth of P. oryzae. However, chloroform stem crude extract of Allamanda cathartica shows greater inhibition zone (60% inhibition) against P. oryzae compared to methanol stem crude extracts (57.5% inhibition) with the radial growth of 1.6 cm and 1.7 cm respectively. The others crude extracts showed slightly antifungal activity against fungal pathogen. Furthermore, the chloroform and methanol stem crude extracts showed stronger inhibitory action than the positive control, Mancozeb® (41% Inhibition). The effective inhibitory concentration of active crude extract was at 7500 ppm. Microscopic observations of antifungal activity of active extracts resulted in hyphal degradation where hyphae were retarded and lysis. The screening of antifungal activity of fractions of active crude extract showed the good antifungal activity was at fraction 4 (70% hexane: 30% ethanol) with the radial growth inhibition 1.8 cm (55% inhibition). The effectiveness of active crude extract in vivo assays were conducted and found that the curative controls were more effective than preventive control.